Legal Protection of Women and Children in the Practice of Nikah Sirri (Unregistered Marriage) - Soraya, Wiranda; Ali, Bukhari; Husnul, Muhammad (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The practice of nikah sirri (unregistered marriage), which still occurs in several regions including Gampong Ajuen, Peukan Bada District, Aceh Besar Regency, raises serious issues, particularly regarding legal protection for women and children. This study aims to describe the practice of nikah sirri in Gampong Ajuen, analyze its impact on legal protection, and identify preventive, mitigative, and solution-oriented measures to minimize its negative consequences. The research applies a qualitative method with a sociological-empirical approach through field data collection. The findings show that nikah sirri creates various problems, such as wives losing their legal rights when abandoned, and children facing difficulties in obtaining birth certificates, legal recognition, and inheritance rights due to the absence of official marriage registration. This situation highlights the legal and social vulnerabilities experienced by women and children as a result of unregistered marriages. To address these issues, strategic measures are required, including public education on marriage registration through the Office of Religious Affairs (KUA), documentation of nikah sirri couples by village authorities, social assistance from DP3A and the Civil Registry Office, and marriage legalization through isbat nikah at the Sharia Court. The contribution of this research is expected to serve as a reference for formulating legal protection policies while strengthening the fulfillment of women’s and children’s rights at both local and national levels.